History and Importance of Land Use and Protection in the North Quabbin Region of Massachusetts (USA) - Alisa D. Golodetz; David R. Foster (Conservation Biology, 1997)
Evaluating the consequences and future of land protection requires broad temporal and spatial perspectives of ecological and cultural factors. We assessed the development of a system of protected areas comprising 37% of central Massachusetts in terms of changing rates and means of land protection. We compared protected areas to the surrounding matrix in terms of physical, biological, and historical features and used these results to raise issues concerning future planning. The rate, purpose, and means of land protection in the North Quabbin Region (168,312 ha) have been dynamic as a result of changes in cultural values and transformation of the landscape from predominantly agriculture to forest. Protected lands are managed by 25 federal and state agencies, private groups, and municipal departments and commissions and are physically and biologically typical of the regional landscape which results from (1) participation of diverse organizations with varied agendas; (2) predominance of large government acquisitions driven by landscape‐scale criteria; and (3) absence of coordination among groups. The large area, relative homogeneity and largely undeveloped status of the North Quabbin Region suggest conservation goals distinct from those in the fragmented and extensively developed neighboring areas of the Connecticut River Valley and Cape Cod and Islands Region. Large tracts of forests, wetlands, and lakes in the North Quabbin Region provide (1) habitat for species requiring extensive, intact areas; (2) the opportunity to maintain broad‐scale ecological processes; (3) connections to regional conservation areas; and (4) recreation. To realize the area’s potential, a comprehensive plan must be based on a broad‐scale perspective and historical understanding of the landscape.